Continuity and innovation in the Aramaic legal tradition - Gross, Andrew D. (Supplements to the Journal for the Study of Judaism, 2008)
Ever since the Elephantine papyri were first published over a century ago, scholars have speculated on the origins of the well-developed legal formularies used in these documents. Since then, many more Aramaic deeds of conveyance both from Elephantine and from elsewhere have been published, especially within the last decade or so. With this expanded text base now available, the time is ripe for a comprehensive re-assessment of these legal formularies. This book endeavors to show that these disparate Aramaic documents, whose chronological scope spans several centuries, form a discrete and coherent tradition. It isolates and identifies the distinctive elements that form the core of this tradition and traces the histories of these elements back through the cuneiform record.